Electromagnetic torque analysis‐based method for performance evaluation and optimisation of closed‐loop CPS regarding small signal stability. Issue 4 (2nd November 2018) - Sheng, Yibiao; Lin, Tao; Chen, Rusi; Chen, Baoping; Ding, Guili; Xu, Xialing; Xie, Chang; Liu, Lin
Abstract : Low frequency oscillation occurs frequently in the smart grid, which threatens the security andstability of the physical system. Wide‐area damping controller (WADC), whichbelongs to cyber system, can effectively suppress inter‐area low frequencyoscillations and improve the small signal stability of the closed‐loopcyber‐physical system (CPS). However, with the introduction of global signals, time delays of communication are inevitable. Considering that, this paperdeduces the general mathematics expression among electromagnetic torquecoefficients, WADC control parameters and time delays, which makes it possibleto analyse the influence mechanism of time delay on small signal stability.Based on these analysis, on the one hand, the time‐delay small signal stabilityregion is established to evaluate the operation state of closed‐loop CPS, on theother hand, if small signal stability is not achieved due to the measured timedelays, optimisation scheme is proposed to carry out WADC control parameterscoordination to optimise small signal stability of the closed‐loop system.Finally, taking two time delays as example, this study verifies theeffectiveness and advantages of the proposed method by comparing the closed‐loopsystem performance considering two time delays with the cases of consideringsinge time delay and without time delay.